Mathematics for Physical Chemistry - Mortimer, Robert G. (New York: Macmillan Publishing, 1981)
Mathematics for Physical Chemistry is the ideal textbook for upper-level undergraduates or graduate students who want to sharpen their mathematics skills while they are enrolled in a physical chemistry course. Solved examples and problems, interspersed throughout the presentation and intended to be students new to the material. The author provides readers with a review of calculus and differential equations that will enable them to succeed in a physical chemistry course. An ideal reference text for practicing chemists as well.
Index 397-405p.